Resistance pattern and maternal knowledge, attitude and practices of suspected Diarrheagenic Escherichia coli among children under 5 years of age in Addis Ababa, Ethiopia: cross sectional study - GebreSilasie, Yeshwondm Mamuye (Antimicrob Resist Infect Control, 2018)
BACKGROUND: Diarrheal illness remains one of the leading causes of morbidity and mortality among children under 5 years of age worldwide, especially in developing countries. Diarrheagenic Escherichia coli (DEC) is the major cause of gastroenteritis in children in the developing world and is associated with high resistance levels to antibiotics. The aims of this study were to isolate and determine susceptibility patterns of DEC among children under 5 years of age with acute diarrhea and to assess maternal knowledge, attitude and practice towards childhood diarrhea. METHODS: A cross sectional study was conducted from August–December 2015 at 3 selected health institutions. Stool samples were cultured and isolated E. coli species were run for antimicrobial susceptibility testing using disk diffusion method. In addition, children’s caretakers were interviewed using structured questionnaires including a Knowledge, Attitude and Practice (KAPs) survey. Bivariate and multivariate logistic regression analysis was used to quantify the effect of different risk factors on bacterial related diarrhea. RESULTS: A total of 253 children, 115 males and 138 females with acute diarrhea were enrolled. E. coli was identified in a total of sixty-one children (24.1%), followed by Shigella (9.1%) and Salmonella (3.95%). Additionally, eighty-six children (34.0%) had parasites identified in stool samples. E. coli isolates showed 83.6% resistance to ampicillin and augmentin followed by, trimethoprim-sulfamethoxazole (62.3%). Multiple resistances were observed in 72.1% of isolates; however, more than 90% of the strains were sensitive to ciprofloxacin and ceftriaxone. Caretakers identified the following as causes of infection: contaminated food and water (83.4%), microorganisms (55.3%), inadequate breast milk (54.1%), teething (45.1%), house flies (43.1%) and evil eye (15.8%). No hand washing before meals and low levels of knowledge had a significant association with E. coli infection (p < 0.05). CONCLUSION: In children with suspected diarrheagenic E. coli, we observed a high frequency of multidrug resistant E. coli. Furthermore, study subjects with low awareness about source, cause and symptoms of the disease were more likely to acquire suspected diarrheagenic E. coli infections. Thus, there is a need for more education in addition to continuous surveillance of the prevalence and antibiotic susceptibility pattern of diarrheal bacterial isolates in hospitals and in the community.